(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Milk is considered as a nearly complete food since it is a good source of protein and major minerals. The consumption of camel and cow milk is becoming more popular, and this is by the perception of the nutritional and therapeutic benefits of the milks. Therefore, the aim of this research is to evaluate the nutrients composition, minerals, vitamins and bio-active components of camel and cow milk. Two samples of camel and cow milk were collected from Katsina central abattoir and transported to Al-Qalam University Katsina Biological Sciences Laboratory and were stored in an icebox. The determination of minerals composition, proximate analysis, Vitamins content and bio-active components were carried out in triplicates using standard analytical procedures. The minerals composition obtained from camel and cow milk were Impressive and Appreciable. The proximate analysis gave a high protein content of 13.00+1.120 in camel milk and 9.00+1.326 in cow milk, Ash content of 14.00+0.06 in camel milk and 18.333+0.577 in cow milk and fat content of (18.700+1.664 in camel and 20.366+0.635 in cow milk and low moisture content of 64.066+3.421 in camel milk and 49.800+2.771 in cow milk respectively. Vitamins content determined shows high content of vitamin c (1.0366+0.0115%) in camel milk and lower 0.960+0.121 in cow milk. the results obtained from bio-active components shows flavonoids, terpenoids and tannins absent, while Alkaloids, steroids and glycosides present. Therefore, camel and cow milk revealed the therapeutic and nutritional properties which are widely exploited for human health.